a)3(x-15)-45=-57 b)(8-x).(x+15)=0

a)3(x-15)-45=-57
b)(8-x).(x+15)=0

2 bình luận về “a)3(x-15)-45=-57 b)(8-x).(x+15)=0”

  1. Giải đáp:
     
    Lời giải và giải thích chi tiết:
    a. 3(x – 15) – 45 = – 57
    ⇒ 3(x – 15) = – 57 + 45
    ⇒ 3(x – 15) = – 12
    ⇒ x – 15 = – 12
    ÷ 3
    ⇒ x – 15 = – 4
    ⇒ x = – 4 + 15 = 11

    b. (8 – x) . (x + 15) = 0
    ⇒ 8 – x = 0 hoặc x + 15 = 0
    ⇒ x = 8 hoặc x = – 15
    ⇒ x ∈ {8; -15}
    \color{orange}text{Xin hay nhất ạ}
    \color{lightblue}text{KhoaOvO}

    Trả lời
  2. Giải đáp:
    a)3(x-15)-45=-57
    3x-45-45=-57
    3x-90=-57
    3x=-57+90
    3x=33
    x=33:3
    x=11
    b)(8-x).(x+15)=0
    $\left[\begin{matrix} 8+x=0\\ x=8\end{matrix}\right.$
    $\left[\begin{matrix} x+15=0\\ x=-15\end{matrix}\right.$
    Vậy x={8;-15}
    Lời giải và giải thích chi tiết:
     

    Trả lời

Viết một bình luận

Câu hỏi mới